2022
DOI: 10.4103/ijd.ijd_871_21
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum 25-Hydroxy Vitamin D Levels and the Severity of Acne Vulgaris

Abstract: Background: Vitamin D is thought to play a role in the pathogenesis of acne, and its levels can change in patients with acne vulgaris. Several studies have revealed that serum 25-hydroxy vitamin D levels tend to be low and statistically significant in acne vulgaris patients. However, the relationship between vitamin D levels and acne severity is still poorly understood. Objective: This study aims to identify the correlation between serum 25-hydroxy vitamin D levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Blood samples of all groups were obtained according to a standardized protocol. A broad laboratory fasting panel including nutritive parameters, such as IGF-1, glucose, insulin, HbA1c, fructosamine, cholesterol, triglycerides, HOMA-index ((insulin[µU/mL] × glucose [mg/dL])/405)) [25], and inflammatory markers (CRP and total leukocyte count), as well as vitamin D and zinc levels, was analyzed [26][27][28].…”
Section: Laboratory Parametersmentioning
confidence: 99%
“…Blood samples of all groups were obtained according to a standardized protocol. A broad laboratory fasting panel including nutritive parameters, such as IGF-1, glucose, insulin, HbA1c, fructosamine, cholesterol, triglycerides, HOMA-index ((insulin[µU/mL] × glucose [mg/dL])/405)) [25], and inflammatory markers (CRP and total leukocyte count), as well as vitamin D and zinc levels, was analyzed [26][27][28].…”
Section: Laboratory Parametersmentioning
confidence: 99%
“…22 In contrast to our finding a systemic review included 10 studies found that all studies (8 of 10) revealed lower serum 25-hydroxy vitamin D levels as the acne severity progresses, although 2 of them were not statistically significant. 23 A small sample size case control study (33 cases and 25 controls receiving vitamin D supplement) in Iraq found that vitamin D deficiency was more frequent in patients with acne, which was inversely related with disease severity, however patient in control group had receive vitamin D supplementation. 24 Another case control study showed vitamin D deficiency is evident in acne vulgaris patients and a statistically significant association with the severity of acne lesions, that included 162 unmarried females only, of 12-30 years of age and Vitamin D levels were sorted as adequate (>30 ng/ml), while in this study the age group was 12-40 years and vitamin D was sorted as sufficient (≥20 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D possesses anti-comedogenic and also antioxidant effects. Consequently, its deficit may promote the development of acne [ 66 ].…”
Section: Reviewmentioning
confidence: 99%
“…The target cells for physiologically active vitamin D metabolites are human sebocytes and keratinocytes, which are reached by nuclear VDRs [ 68 ]. It has been noted that vitamin D3 inhibits keratinocyte proliferation and promotes keratinocyte differentiation [ 66 ]. This is explained by the VDR-mediated genetic effect that causes an arrest of sebocytes in the G1 phase, which in turn prevents cell proliferation [ 69 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation